Visual discrimination of dihydroxybenzene isomers based on a nitrogen-doped graphene quantum dot-silver nanoparticle hybrid. Issue 41 (1st October 2015) - Shi, Bingfang; Su, Yubin; Zhao, Jingjin; Liu, Rongjun; Zhao, Yan; Zhao, Shulin
Abstract : A stable N-GQD/AgNP hybrid was prepared using Ag + as the precursor and N-GQDs as the reducing agent and stabilizer, and this nanohybrid was used for the visual discrimination of dihydroxybenzene isomers. Abstract : A room temperature reducing agent-free strategy for the synthesis of a nitrogen-doped graphene quantum dot-silver nanoparticle (N-GQD/AgNP) hybrid was presented. In this strategy, N-GQDs were used as a reducing agent and stabilizer for the formation of the N-GQD/AgNP hybrid, and the formation of the N-GQD/AgNP hybrid may result from the extraordinary reduction properties of N-GQDs, which are attributed to the nature of the surface oxygen-containing functional groups. The N-GQD/AgNP hybrid exhibits good dispersity and outstanding catalytic ability toward the oxidation of catechol (CC) and hydroquinone (HQ) by Ag + . In the presence of the N-GQD/AgNP hybrid, the reduction of Ag + by CC and HQ was improved. CC enhanced the absorbance of the N-GQD/AgNP-Ag + system the most, and HQ followed, while resorcinol (RC) had only a little effect on the absorption intensity of the system. Thus, a sensitive and selective colorimetric sensing method based on the N-GQD/AgNP-Ag + system was developed for the discrimination of CC, HQ and RC. A good linear relationship was obtained from 0.1 to 15.0 μM for CC and from 0.3 to 20.0 μM for HQ. The detection limits of CC and HQ were 0.03 and 0.1 μM, respectively. In addition, the proposed method also shows a high selectivity for the detection of CC and HQ, and appreciable changes in color of the N-GQD/AgNP-Ag + system toward CC, RC and HQ were observed.